2019
DOI: 10.1177/0042085919842625
|View full text |Cite
|
Sign up to set email alerts
|

Formative Learning Experiences of Urban Mathematics Teachers’ and Their Role in Classroom Care Practices and Student Belonging

Abstract: Mathematics teachers’ preteaching experiences as mathematics learners can affect their identity and practice in supporting their own students’ learning and motivation in mathematics. However, little empirical data exist on teachers’ formative experiences to guide these assumptions, particularly how teachers draw on these experiences when teaching, motivating, and caring for underserved students of color. This exploratory sequential mixed-methods study examines the formative mathematical experiences of 12 teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This includes self-confidence, a sense of comfort, and a sense of ownership of the mathematical discipline. Someone who feels that they belong to mathematics tends to think that they have the ability and potential to learn and succeed in mathematics (Matthews, 2020). Factors such as social support, an inclusive learning environment, and positive experiences in mathematics can influence one's feelings of belonging (Darragh, 2013).…”
Section: Terminology and Conceptsmentioning
confidence: 99%
“…This includes self-confidence, a sense of comfort, and a sense of ownership of the mathematical discipline. Someone who feels that they belong to mathematics tends to think that they have the ability and potential to learn and succeed in mathematics (Matthews, 2020). Factors such as social support, an inclusive learning environment, and positive experiences in mathematics can influence one's feelings of belonging (Darragh, 2013).…”
Section: Terminology and Conceptsmentioning
confidence: 99%
“…Gray et al (2018) detailed the interpersonal, instructional, and institutional opportunities that support the development of school belonging among ethnic-racial minority youth. Conway-Turner et al (2020) and Matthews (2020) focus on the role of teachers and instruction in promoting academic success and feelings of belonging among students. While Conway-Turner et al (2020) argue a possible race match between teachers and students for more favorable outcomes, Matthews (2020) found that teacher reports of emotional and instructional support were associated with students' sense of belonging.…”
Section: School Belonging As a Buffer In Majority White Schoolsmentioning
confidence: 99%
“…Conway-Turner et al (2020) and Matthews (2020) focus on the role of teachers and instruction in promoting academic success and feelings of belonging among students. While Conway-Turner et al (2020) argue a possible race match between teachers and students for more favorable outcomes, Matthews (2020) found that teacher reports of emotional and instructional support were associated with students' sense of belonging. Taking together previous research and findings from the present study, we note that it is imperative to consider the racial context of Black youths' schools when seeking to understand the effects of racial discrimination stress and school belonging on academic attitudes and beliefs, particularly when identifying protective factors.…”
Section: School Belonging As a Buffer In Majority White Schoolsmentioning
confidence: 99%
“…Teachers can develop an ethic of perseverance through the experience of formative assessment that they carry out, which is closely related to the science identity that the students are studying. However, teachers' understanding of what enables students to persevere through challenging assignments shows apparent differences in the emotional and instructional support techniques teachers provide in classrooms [31]. Thus, teachers need to master various socio-emotional teaching techniques [32] to carry out differentiated learning.…”
Section: Introductionmentioning
confidence: 99%